The Ghana reader : history, culture, politics - Konadu, Kwasi; Campbell, Clifton C. (World readers., 2016)
Covering 500 years of Ghana's history, The Ghana Reader provides a multitude of historical, political, and cultural perspectives on this important West African nation, emphasizing Ghana's enormous symbolic and pragmatic value to global relations and its ethnic and cultural diversity.